TANGGUNG JAWAB PELAKU USAHA TERHADAP KONSUMEN PADA MAKANAN KEMASAN YANG TELAH KADALUARSA MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Arif Duwi Saputra (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACTConsumer convenience in consuming a food product is a particular concern for consumers in particular and producers in general. Many considerations made by consumers in consuming a product specifically food products so that consumers get comfort and safety. These considerations include what ingredients are contained in food products, nutritional content in food products, food processing during the production, storage, packaging, halality, and expiration period of a food product. The number of food products circulating in the community without regard to the provisions regarding the inclusion of expired labels is considered to be unsettling consumers. Law Number 8 of 1999 concerning Consumer Protection Article 4 explains that one of the rights of consumers is the right to comfort, security and safety in consuming goods and or services.The method used in this study is the empirical juridical method, the type of data used in this study comes from primary data, that is data collected and processed by the researcher directly from the subject or object of research and secondary data, ie the data obtained is not directly from research object or subject. The problem that the author discusses in this thesis is the responsibility of Business Actors for expired packaged food according to Law Number 8 of 1999 Concerning Consumer Protection and Handling Performed by BPSK Against Cases That Occur in the Field of Expired Packaged Foods.Based on the research results, it can be concluded that the form of business actor's responsibility as referred to in Article 19 of Law Number 8 of 1999 concerning Consumer Protection is to provide compensation to consumers both in the form of products of the same price or in the form of other compensation agreed between the seller and Buyers, such as providing care costs for consumers whose health is impaired and Handling Cases that Happen in the Field in real terms is the absence of business actors who resolve their disputes with consumers in the District Court or BPSK, in general it can be stated as a consequence of consumer attitudes that always avoid conflict. Pursuant to Law Number 8 of 1999 concerning Consumer Protection, every injured consumer can settle his dispute through: Judiciary in the general court environment which refers to the applicable provisions in the District Court and Settlement of offenses outside the court. Just as the District Court is a place where people seek justice so too is BPSK. Therefore, every person in dispute will submit their claim to the district court or BPSK to get their rights, especially when expired packaged food consumers are disadvantaged if they want to. Keywords: Consumers, Business Actors, Expiration, Consumer Disputes